Relative Risk of Intimate Partner Violence According to Access to Instrumental Social Support Among Pregnant Women in Eswatini Whose Partners Do and Do Not Drink Alcohol - Fielding-Miller, Rebecca (Journal of interpersonal violence, 2022)
Intimate partner violence (IPV) affects one in three women around the world and is the tenth leading cause of death for women in Africa aged 15 to 29?years. Partner alcohol use, access to social support, and poverty all affect women?s likelihood of experiencing violence. We sought to understand how partner alcohol use differentially affected the hypothesized association between a protective role of instrumental social support (in the form of food or financial loans) against IPV for a clinic-based sample of women in the Kingdom of Eswatini (formerly known as Swaziland). We use cross-sectional data from a parent study of women recruited from urban and rural antenatal clinics in Eswatini (n?=?393) to calculate the association between experiencing IPV and perception of one?s ability access to large cash loans, small cash loans, and food loans?both for the full sample and stratified by partner alcohol use. In fully adjusted models, the perception that one could access loans of food or money was associated with decreased relative risk of IPV for all women. These associations were modified by partner alcohol use. Access to instrumental support (loans of food or money) is associated with decreased risk of IPV, but this association varies according to the type of loan and whether or not a woman?s partner drinks alcohol. Economic empowerment interventions to reduce IPV must be carefully tailored to ensure they are appropriate for a woman?s specific individual, relationship, and community context.